The Effect of Using Digital Posters Based on Canva Application on Students’ Writing Ability in Narrative Text at Senior High School - Salsabila, Syarifah (Institut Agama Islam Negeri Palopo, 2023)
Digital posters are visually appealing and can capture students' attention more effectively than traditional teaching materials, while Canva offers a wide range of design tools and templates, allowing students to express their creativity in designing posters. Hence, digital poster creation on the Canva application is suitable as instructional media. This study aims to investigate the effect of using digital posters based on the Canva application on students’ writing ability in narrative text at SMAN 6 Pekanbaru. This study uses a quasi-experimental research design where the experimental group receives a digital poster based on the Canva application as the instructional media while the control group receives conventional instructional media. The population of this study is the tenth-grade students of SMAN 6 Pekanbaru. The purposive sampling is the type of sampling technique in this study where 36 students from X MIPA 2 as the control group and 34 students from X MIPA 4 as the experimental group. The data were collected from a pretest-posttest of writing narrative text before and after treatments. The hypothesis test was conducted using the Mann-Whitney test. The result displays the alternative hypothesis (Ha), the Asymp. Sig. (2-tailed) is 0.001<0.05. Therefore, using digital posters based on Canva application has a significant effect on students’ writing ability in narrative text at SMAN 6 Pekanbaru. It is suggested to use digital poster based on Canva application as instructional media for teachers, students, and researchers. Canva can spark creativity, improve design and writing skills, and create engaging learning materials.